Komparasi Model Pembelajaran Problem Based Learning dan Project Based Learning Terhadap Hasil Belajar Siswa Pada Materi Perangkat Keras Jaringan Internet Kelas IX SMP Negeri 5 Sungai Kakap Kabupaten Kubu Raya - Lestari, Isnania; Juanda, Raja (Efektor, 2019)
The purpose of this study was to find out: 1) Student learning outcomes after applied Problem Based Learning learning models on network hardware material. 2) Student learning outcomes after the Project-Based Learning learning model is applied to internet network hardware material. 3) Student learning outcomes after being applied to Problem Based Learning learning models are better than student learning outcomes after the Project-Based Learning learning model is applied to internet network hardware material. The method used in this study was an experimental method, with a two-group design posttest only, with a population of 60 students consisting of two classes, and the number of samples for the experiment was 30 students and 30 students controlled. The data collection technique used is the essay test. The conclusions are: 1) The average student learning outcomes after the implementation of the Problem Based Learning learning model on internet network hardware material is 79.17. 2) The average student learning outcomes after being applied to the Project-Based Learning learning model on the internet network hardware material is 75.00. 3) Problem-based learning is better than project-based learning in internet network hardware material on student learning outcomes seen from the significance value of 0.038 smaller (<) than 0.05.